Simulation of an Economic Policy on Second Life Using a Conjunctural Analysis Approach - Yrina JANVIER (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2007)
This paper intends to define an economic policy that does notcompromise the coordination between the 4 main sectors of an economy: the real sector, the public sector, the exterior sector and the monetary sector. The subject is Second Life (SL) a totally virtual world that is starting to occupy a great economicplace especially with e-commerce. For doing so, some data are arbitrarily chosen as done and projections are made from them. Data are expressed in billion of Linden dollars.